Endothelial Mineralocorticoid Receptor Mediates Parenchymal Arteriole and Posterior Cerebral Artery Remodeling During Angiotensin II–Induced Hypertension - Diaz-Otero, Janice M.; Fisher, Courtney; Downs, Kelsey; Moss, M. Elizabeth; Jaffe, Iris Z.; Jackson, William F.; Dorrance, Anne M. (Hypertension (Dallas, Tex. 1979), 2017)
The brain is highly susceptible to injury caused by hypertension because the increased blood pressure causes artery remodeling that can limit cerebral perfusion. Mineralocorticoid receptor (MR) antagonism prevents hypertensive cerebral artery remodeling, but the vascular cell types involved have not been defined. In the periphery, the endothelial MR mediates hypertension-induced vascular injury, but cerebral and peripheral arteries are anatomically distinct; thus, these findings cannot be extrapolated to the brain. The parenchymal arterioles determine cerebrovascular resistance. Determining the effects of hypertension and MR signaling on these arterioles could lead to a better understanding of cerebral small vessel disease. We hypothesized that endothelial MR signaling mediates inward cerebral artery remodeling and reduced cerebral perfusion during angiotensin II (AngII) hypertension. The biomechanics of the parenchymal arterioles and posterior cerebral arteries were studied in male C57Bl/6 and endothelial cell–specific MR knockout mice and their appropriate controls using pressure myography. AngII increased plasma aldosterone and decreased cerebral perfusion in C57Bl/6 and MR-intact littermates. Endothelial cell MR deletion improved cerebral perfusion in AngII-treated mice. AngII hypertension resulted in inward hypotrophic remodeling; this was prevented by MR antagonism and endothelial MR deletion. Our studies suggest that endothelial cell MR mediates hypertensive remodeling in the cerebral microcirculation and large pial arteries. AngII-induced inward remodeling of cerebral arteries and arterioles was associated with a reduction in cerebral perfusion that could worsen the outcome of stroke or contribute to vascular dementia.